2015
DOI: 10.1039/c5tc00628g
|View full text |Cite
|
Sign up to set email alerts
|

High rate fabrication of room temperature red photoluminescent SiC nanocrystals

Abstract: Table of contents entrySiC nanocrystals with room temperature red region photoluminescence are fabricated at high rate in atmospheric pressure thermal plasma using SiCl4 and C2H2 as silicon source and carbon source. AbstractHigh rate fabrication of thin film complex consisting of cubic-SiC nanocrystals, amorphous silicon and graphite was realized by an atmospheric pressure thermal plasma enhanced chemical vapor deposition (APTPECVD) process with SiCl4 and C2H2 as silicon source and carbon source, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…Surface modifications based on coordination reaction between transition metals and organic molecules with thiol, carboxylic, hydroxy, or amino groups have also been reported. For example, Cheng et al reported the fabrication of robust superhydrophobic films on porous copper substrates based on acid etching, replacement reaction (denoted as Cu@Ag), and further n ‐dodecanethiol (DDT) modification (denoted as Cu@Ag@DDT) . Based on a similar synthetic mechanism, Wang et al fabricated excellent underwater super oil‐repellent interfaces based on the coordination reaction between tannic acid (TA) and coppers …”
Section: Surface Modification Of the Micro‐/nanostructurementioning
confidence: 99%
“…Surface modifications based on coordination reaction between transition metals and organic molecules with thiol, carboxylic, hydroxy, or amino groups have also been reported. For example, Cheng et al reported the fabrication of robust superhydrophobic films on porous copper substrates based on acid etching, replacement reaction (denoted as Cu@Ag), and further n ‐dodecanethiol (DDT) modification (denoted as Cu@Ag@DDT) . Based on a similar synthetic mechanism, Wang et al fabricated excellent underwater super oil‐repellent interfaces based on the coordination reaction between tannic acid (TA) and coppers …”
Section: Surface Modification Of the Micro‐/nanostructurementioning
confidence: 99%
“…Naturally, the stacking sequence of 3C‐SiC unit cells was arranged as ABCABC…, but it transformed into the multiple layer inclusion of other polytypes because of the abundant stacking faults introduced, so that a stacking pattern‐α‐SiC such as ABAB … (2H), ABCBABCB … (4H) occurred . From 200 to 350 mm, two broader features between 200 and 500/cm were also observed in the overlapping of the transverse acoustic (TA) and the longitudinal acoustic (LA) of the pseudo‐α‐SiC, respectively . In addition, features between 500 and 600/cm originated from the amorphous silicon (a‐Si) TO mode (520/cm) .…”
Section: Resultsmentioning
confidence: 97%
“…In addition, features between 500 and 600/cm originated from the amorphous silicon (a‐Si) TO mode (520/cm) . The band peaks at 1350 and 1580/cm corresponded to graphite's D band and G band . Only graphite peaks were detected in the tube between 150 and 200 mm, but the XRD patterns in Figure indicate the presence of SiC in the coating.…”
Section: Resultsmentioning
confidence: 99%
“…These hydrogels are considered superhydrophobic or superoleophilic materials that repel water while allowing oil to enter its matrix . Many studies have shown the use of super‐wettable materials for oil removal such as the mesh fabrication using hydrogel coatings . This includes the usage of a biodegradable deacetylated koniac glucomannan (KGM) (DKGS) coat that has a 97.5% oil‐removal rate .…”
Section: Introductionmentioning
confidence: 99%
“…The use of a thermoresponsive hydrogel‐coated mesh has also been studied for controlled oil–water separation, where the mesh's swelling decreased due to the reduced water retention upon reaching LCST . These meshes use gravity separation to allow water to permeate through the polymerized hydrogel‐coated membrane, while trapping the oil behind …”
Section: Introductionmentioning
confidence: 99%